2010
DOI: 10.1088/2041-8205/720/2/l144
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Far-Infrared Counterparts of Bright Submillimeter Galaxies Using Pacs Imaging

Abstract: We present a search for Herschel-PACS counterparts of dust-obscured, high-redshift objects previously selected at submillimeter and millimeter wavelengths in the Great Observatories Origins Deep Survey North field. We detect 22 of 56 submillimeter galaxies (39%) with a SNR of ≥ 3 at 100 µm down to 3.0 mJy, and/or at 160 µm down to 5.7 mJy. The fraction of SMGs seen at 160 µm is higher than that at 100 µm. About 50% of radio-identified SMGs are associated with PACS sources. We find a trend between the SCUBA/PAC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 47 publications
3
23
1
Order By: Relevance
“…The detection of this source in the PACS bands has also been discussed by Dannerbauer et al (2010) and Magnelli et al (2010) while Frayer et al (2008) has reported the detection of CO(2→1) emission. In Fig.…”
Section: Evidence For Silicate Absorptionsupporting
confidence: 60%
“…The detection of this source in the PACS bands has also been discussed by Dannerbauer et al (2010) and Magnelli et al (2010) while Frayer et al (2008) has reported the detection of CO(2→1) emission. In Fig.…”
Section: Evidence For Silicate Absorptionsupporting
confidence: 60%
“…The secure PACS 160 μm counterpart seems to be physically associated with the HAE. No other SMG in our sample has two PACS counterparts and no such system was seen in GOODS-N (Dannerbauer et al 2010). At the edge of the PACS 160 μm beams, we find the candidate Lyα emitters L877 (Kurk et al 2004a).…”
Section: Smm J1140424−262715 (Dkb14 No)mentioning
confidence: 62%
“…For each candidate counterpart within the search radius we calculate the corrected Poissonian probability p that the SMG association is a chance coincidence. This approach corrects the simple Poissonian probability of a detected association for the possibility of associations of different nature but similar probability (Downes et al 1986) and is widely applied and accepted in the community (e.g., Ivison et al 2002;Dannerbauer et al 2004Dannerbauer et al , 2010Biggs et al 2011;Smail et al 2014). It basically depends on the search radius, the distance of the potential counterpart to the LABOCA source and the source surface density down to the flux level of the potential LABOCA counterpart.…”
Section: Laboca Source Counterpartsmentioning
confidence: 99%
“…In other fields, the PACS/SPIRE requirement is even less constraining because the SPIRE observations are as deep as in GOODS-N while radio and (sub)mm observations are shallower. This is reflected by the fact that the PACS/SPIRE detection rate of SMGs with robust spectroscopic redshift estimates is very high, and much higher than that observed by Dannerbauer et al (2010) for the entire SMG population, i.e., 73% versus 39%.…”
Section: Final Sample and Selection Biasesmentioning
confidence: 94%